Coulomb Stress Analysis of the West Coast Sumatra Earthquake on Mount Imun and Mount Helatoba - Sinaga, Goldberd Harmuda Duva; Nainggolan, Juliper; Pardede, Hebron (Department of Physics Education, Universitas Mataram, 2025)
The island of Sumatra is a meeting area between the Indian Ocean plate in the South and the southwest edge of the Sunda Exposure, which is also the continental plate of Southeast Asia or the Eurasian Plate. The meeting of the plates makes the island of Sumatra an area prone to tectonic earthquakes, including Mount Imun and Helatoba which are located in the Tarutung basin. This study uses the Mohr-Coulomb model in the analysis of changes in coulomb stress. This modeling uses data from earthquakes that occurred on the West Coast of Sumatra which was then processed in coulomb 3.4 software. This modeling resulted in stress distribution in Imun and Helatoba. Coulomb stress changes until this time in Imun is 0.323 bar (2024) and coulomb stress change in Helatoba is 0.217 bar. The effect of the increase in coulomb stress (red lobe) originating from the earthquake on the west coast of Sumatra is triggering 2 tectonic earthquakes at the coordinates of Mount Imun in 2022 and triggering a tectonic earthquake at the coordinates of Helatoba in 2018.